Factors That Affect the Disaster Preparedness of Emergency Nurses in Public Health Center - Suaida, Desi Holifatus; Handayani, Dian; Suryanto, Suryanto (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
Disasters can result in damage to infrastructure, material losses, and even death. Nurses have an important role in disaster management, especially those who work in the emergency room. This study aims to determine the relationship between the length of work, education level, disaster training, response phase, self-efficacy, infrastructure, and family support with disaster preparedness. This study used a cross-sectional design. The sample is 96 nurses, the sampling technique uses Total Sampling and the analysis uses the Spearman Rank test. The results of this study indicate that there is no relationship between length of service (p-Value = .148, r = .149), level of education (p-Value = .460, r = .076), response phase (p-Value = .410, r = - .085), whereas disaster training (p-Value = .009, r = .265), self efficacy (p-Value = .000, r = .702), infrastructure (p-Value = .000, r = .603), support families (p-Value = .003, r = .298) with disaster preparedness. There is no relationship between the length of work, level of education, and response phase with disaster preparedness. while disaster training, self-efficacy, infrastructure, and family support have a relationship with disaster preparedness. Health centres need to prepare infrastructure because they can be a supporting factor in increasing the readiness of nurses in disaster management.Abstrak: Bencana dapat mengakibatkan kerusakan infrastruktur, kerugian material bahkan menyebabkan kematian. Perawat memiliki peran penting dalam manajemen bencana terutama yang bekerja di IGD. Penelitian ini bertujuan untuk mengetahui hubungan lama kerja, tingkat pendidikan, pelatihan bencana, fase respon, self efficacy, sarana prasarana dan dukungan keluarga dengan kesiapsiagaan bencana. Penelitian ini menggunakan desain cross sectional. Sampel sebanyak 96 Perawat, teknik sampling menggunakan Total Sampling dan analisis menggunakan uji Spearman Rank. Hasil penelitian ini menunjukkan tidak ada hubungan antara lama kerja (p Value = .148,  r = .149), tingkat pendidikan (p Value = .460,  r = .076), fase respon (p Value = .410,  r = - .085), sedangkan pelatihan bencana (p Value = .009,  r = .265), self efficacy (p Value = .000,  r = .702), sarana prasarana (p Value = .000,  r = .603), dukungan keluarga (p Value = .003,  r = .298) ada hubungan dengan kesiapsiagaan bencana. Tidak terdapat hubungan lama kerja, tingkat pendidikan dan fase respon dengan kesiapsiagaan bencana sedangkan pelatihan bencana, self efficacy, sarana prasarana dan dukungan keluarga terdapat hubungan dengan kesiapsiagaan bencana. Puskesmas perlu mempersiapkan sarana  prasarana karena dapat menjadi faktor pendukung dalam meningkatkan kesiapan perawat dalam manajemen bencana.